Edukasi Perencanaan Sanitasi Rumah Tinggal Sederhana untuk Meningkatkan Kuliatas Hidup Masyarakat Desa Dawuhan Kecamatan Wanayasa Kabupaten Banjarnegara - Andri Andriawan; Muhammad Ramahani Suryolaksono; Irfauzi Firman Hidayat; Dwi Retno Astutik (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This activity aims to create a healthy and high-quality living environment through planning simple household sanitation systems to improve the welfare and quality of life of the people in Dawuhan Village, Wanayasa District, Banjarnegara Regency. The main challenge faced during this activity is that the community in Dawuhan Village tends to be less concerned about health related to sanitation for several reasons. First, the lack of knowledge and awareness about the importance of having proper latrines and sanitation causes them to be unaware of the negative impacts on health, such as the risk of waterborne diseases or contamination of the environment. The methods used in this community service program include surveys, observations, socialization/training, assistance, monitoring, and evaluation. The pre-test results showed an average score of 65.00, while the post-test results showed an average score of 85.33. The post-test results indicate an increase after providing education related to healthy and environmentally conscious household sanitation.